Clinical value of 24-hour urinary sodium determination in children with postural tachycardia syndrome - Li, Jiawei (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2015)
OBJECTIVE: To analyze the clinical value of 24-hour urinary sodium determination in children with postural tachycardia syndrome (POTS)